Slot Pole Study of Field Excitation Flux Switching Machines Using Segmental Rotor and Non-Overlap Windings - F. Omar, M; Sulaiman, E; A. Soomro, H; I. Jusoh, L; Amin, F (International Journal of Engineering and Technology, 2018)
Field excitation flux switching machines (FEFSMs) in which their torque performance generated by interaction between armature and field excitation (FE) coils have been widely designed and developed for various applications. In this regard, FEFSM with salient rotor is considered the most suitable candidate for high speed applications because of their advantages of flux controllability, and robust due to single piece of rotor structure. However, the existing FEFSM with overlapped armature and FEC windings lead to increment of copper loss, motor size and material cost. In addition, the declination of torque and power densities due to high rotor weight needs to be improved. In this paper, performance comparisons of four FEFSM topologies particularly emphasis on non-overlap armature coil and FEC windings placed on the stator with segmental rotor are investigated. The performances, including flux linkage, back-emf, flux strengthening, flux line, flux distribution, cogging torque, torque and power of the proposed motor are analysed and compared using 2D finite element analysis (FEA) thru JMAG Designer version 15. As a result, segmental rotor has produced shorter flux paths, while non-overlapping windings has reduced the copper consumption. Finally, the best combination of stator slot-pole configurations is 12S-6P which provide high flux linkage, high torque and power of 0.0412 Wb, 0.77 Nm and 0.26 kW, respectively.Â